Exploring the Export-Growth in Nepal: A Time Series Analysis Using the ARDL Model - Kadel, Suren B.; Bhusal, Tara Prasad (Molung Educational Frontier, 2026)
This study examines the relationship between economic growth and trade in Nepal using time series data. The research determines trade to be a crucial impetus to economic development and examines economic growth's contribution to Nepal's export performance. The study applies the autoregressive distributed lag (ARDL) technique to examine long-run and shortrun relationships between key macroeconomic indicators, including gross domestic product (GDP), population, and import. The estimated log-linear ARDL results show that GDP and population carry negative coefficients, indicating that Nepal’s economic and demographic growth have not translated into export expansion due to the dominance of non-tradable sectors, labor emigration, and structural inefficiencies, while the positive import coefficient confirms the import-dependent nature of export production. The tests establish the data points to be stable, normally distributed, and devoid of serial correlation and heteroskedasticity. The research concludes by calling to make policies that favour economic growth to enhance trade performance. The research recommends policy measures, including infrastructure investments, trade diversification, and better governance, to expand Nepal's export sector and attain sustainable economic development.